Religious capital and religious rewards: A study in the economics of religious life - Flere Sergej (Panoeconomicus, 2012)
Religious life is studied by way suggested by the rational choice theory and the religious capital theory. The basic contentions of the theory on the nature of religious life having to do with an exchange upon a religious market, by firms offering compensators and rewards, and consumers, is considered. In the empirical analysis, it was validated that the independent (religious capital) and dependent (religious rewards of two types) were empirically separate constructs. Cross-sectional analysis of survey data indicated a very strong association between religious capital and institutional and ritual experience rewards within religious life, at a cross-cultural analysis, including Bosnian Muslims, Serbian Orthodox, Slovenian Catholics and US Protestants. The association was confirmed as robust at regression inspection with religious socialization. This extends further support for the empirical validity these novel theories of religious life and extensions of economic analysis into religious life.